HASIL LUARAN JANIN PADA IBU DENGAN RIWAYAT ABORTUS - Ningrum, Ema Wahyu (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: FETAL OUTCOME OF MOTHER WITH THE HISTORY OF ABORTION Approximately 80-90 % of women who had experienced a spontaneous abortion once or twice have babies mature in subsequent pregnancies . The risk of spontaneous abortion increases with the increase in the number of parity , maternal age and fetal. Purpose: To find out mother characteristics and fetal outcome of mother with the history of abortion at General Hospital Cilacap.  Method  :The study method used was descriptive, by used secondary data from Department of Obstetric and Gynaecology and Medical Record General Hospital Cilacap. The variable was age, parity,birth interval. Fetal outcome consist of premature, Low Birth Weight (LBW), mature and abortion. Result:The highest of mother with history of abortion at the age 25-29 years old 38,39%,  parity 2-3 46,43%, birth interval < 24 months 64,29%. Fetal outcome consist of mature 75,89%, premature 11,61%, LBW 10,71%, abortion 1,79%. The risk of non mature outcome at the age 15-19 and 35-39 years old 1-4 times bigger than 20-24 years old, parity 1 and ≥ 4 1-2 times bigger than parity 2-3, birth interval ≥ 24 months 1 times bigger than < 24 months. Conclusion: The mother with the history of abortion, it was mostly at age 24-25 years old, parity 2-3, birth interval < 24 months. The risk of non mature outcome mostly at the age 15-19 and 35-39 years old, parity 1 and ≥ 4, birth interval ≥ 24 months.  Keyword: The History of Abortion, Mother Characteristics, Birth Interval, Fetal Outcome